2018
DOI: 10.1021/acs.jpcb.8b05053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intense Electric Fields on the Double Proton Transfer in the Watson–Crick Guanine–Cytosine Base Pair

Abstract: The double proton transfer reaction in the guanine-cytosine (GC) base pair is studied, using density functional theory, to understand the chances of mutations under the effect of uniform electric fields in the order of 10 to 10 V m. On the basis of potential energy surfaces, reaction Gibbs energies, equilibrium constants, imaginary frequencies, forward and reverse barrier heights, tunneling-corrected rate constants, half-lives of the forward and reverse reactions, percent tautomerization, and Boltzmann distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 36 publications
(79 reference statements)
3
56
0
Order By: Relevance
“…Céron-Carrasco et al [50] have shown that the inclusion of base pair stacking and explicit solvation causes the double proton transfer equilibrium constant to be smaller than that in the gas phase. In corroboration with their findings, we report equilibrium constants to be one order of magnitude smaller than recent QMonly gas phase studies that have used B3LYP/6-311++G** (1.68 × 10 −8 ) and MP2/aug-cc-pvTZ (7.5 × 10 −8 ) methods [13,15].…”
Section: G:c Tautomerismsupporting
confidence: 89%
See 3 more Smart Citations
“…Céron-Carrasco et al [50] have shown that the inclusion of base pair stacking and explicit solvation causes the double proton transfer equilibrium constant to be smaller than that in the gas phase. In corroboration with their findings, we report equilibrium constants to be one order of magnitude smaller than recent QMonly gas phase studies that have used B3LYP/6-311++G** (1.68 × 10 −8 ) and MP2/aug-cc-pvTZ (7.5 × 10 −8 ) methods [13,15].…”
Section: G:c Tautomerismsupporting
confidence: 89%
“…These are in good agreement with the values of approximately 1 kcal mol −1 computed using BP86/6-311++G** [42]. Other studies, however, reported reverse free energy barriers less than 0 kcal mol −1 using MP2/aug-cc-pVTZ and B3LYP/ 6-311++G** [13,15].…”
Section: G:c Tautomerismsupporting
confidence: 86%
See 2 more Smart Citations
“…44,[79][80][81] A seminal study by Shaik and co-workers demonstrated that not only can an EEF lower or raise the barrier for a Diels-Alder reaction when oriented in one direction or the other along the "reaction axis"-that is, the (approximate) axis along which electrons reorganize (on average) to make and break bonds-but an electric eld oriented perpendicular to the reaction axis can induce endo/exo selectivity. 82 The potential for EEFs to control chemical transformations has captured the curiosity of many groups [83][84][85][86][87][88][89][90][91][92] since Coote and co-workers experimentally demonstrated electrostatic catalysis of a Diels-Alder reaction in 2016. 93 For example, a recent experimental study demonstrated EEF-induced selective catalysis in a twostep reaction.…”
Section: External Electric Eldsmentioning
confidence: 99%